Various drying techniques for conversion of extracted chicken feather keratin solution to powder - Alberto, V.; Gupta, Arun (Universiti Malaysia Pahang, 2022)
Keratin powder is produced from the drying of keratin solution extracted from chicken feathers. Powdered form of keratin protein eases the storage and transport of keratin and can be further developed into nutrient supplements. The objective of this research is to convert liquid keratin obtained from chicken feathers into powder through different methods and also to identify the effects of various drying methods on the keratin sample. Liquid keratin was converted into solid particles through spray drying, freeze drying and vacuum-oven drying where the products were visually observed and analysed using FTIR and SEM to determine the effects of the drying methods on the keratin sample. The SEM results show that the product of spray drying produced smaller spherical particles with diameter ~3µm-17µm while freeze drying and vacuum-oven drying produced coarse, flaky irregular-shaped particles with diameter ~70µm-470µm and ~100µm530µm respectively. FTIR spectroscopy shows that the keratin samples remained their characteristics as a true protein including spray drying when encapsulated with Arabic gum even at high temperatures up to 110°C. Conclusively, spray drying should be considered for future development of keratin as a nutrient supplement while freeze drying and vacuum-oven drying for storage and transport of keratin